Penyuluhan Kewirausahaan, Marketing Mix Dan Produksi Pada Umkm Kelap Kopi Lama Johor Bahru - Yentisna .; Alfin Alvian; Yofina Mulyati; Tri Sukma; Nini .; Prima Yulianti; Masruri .; Dewi Sartika; Idwar .; Ratnawati Raflis; Likanopa Syentia; Ridho Deza Perkasa (Jurnal Imiah Pengabdian Pada Masyarakat (JIPM), 2026)
Kelab Kopi Lama is one of the micro, small, and medium enterprises (MSMEs) in the culinary sector that adopts a traditional kopitiam concept while maintaining the classic taste of traditional foods and the atmosphere of an old coffee shop in Kempas, Johor Bahru. The increasingly competitive culinary industry requires business actors to develop product differentiation and marketing strategies that can attract and retain customers. This study aims to analyze the characteristics of Kelab Kopi Lama as a culinary MSME through product variety, business concepts, and marketing strategies implemented to maintain customer interest. This study uses a descriptive approach through observations of products, services, and business marketing activities. The results show that Kelab Kopi Lama has competitive advantages through its diverse menu offerings, including traditional kopitiam sets such as toast, half-boiled eggs, and Kopi O, as well as signature dishes such as Nasi Dagang, Putu Mayam, Nasi Padang with various side dishes, Nasi Lemak Kukus Basmathi, Lontong, Curry Noodles, Laksa Johor, and various traditional snacks. In addition to product diversity, the traditional kopitiam concept provides added value by strengthening business identity and enhancing customer experiences. The combination of product innovation, quality food offerings, and cultural culinary values contributes to maintaining business sustainability. This study highlights that the implementation of marketing mix strategies and product diversification can be effective approaches for culinary MSMEs to improve competitiveness and build customer loyalty.